Cluster Preface: Atropisomerism - Siegel, Jay S. (Synlett, 2018)
Jay S. Siegel received his Ph.D. from Princeton (1985), was a Swiss Universities Fellow at ETH Zurich (1983-4), and NSF–CNRS postdoctoral fellow at the University of Louis Pasteur in Strasbourg (1985-6). He began as Assistant Professor of Chemistry (1986) at UCSD, was promoted to Associate Professor (1992) and Full Professor (1996). In 2003, he was appointed as Professor and co-director of the Organic chemistry institute of the University of Zurich (UZH) and Director of its laboratory for process chemistry research (LPF). He served as Dean of Studies and Head of the Research Council for the Faculty of Sciences at UZH. He moved to Tianjin University in 2013 as dean and joined the Schools of Pharmaceutical and Life Sciences into a new Health Science Platform. His research is in the area of Stereochemistry and Physical Organic Chemistry.